The Relationship Between Parenting Style and Social Behavior of Early Childhood in Bukit Kemuning Subdistrict, Batang Hari Regency, Jambi Province - Amalia, Ledi; Aini, Wirdatul (Universitas Negeri Padang, 2026)
This research is based on the low social behavior of early childhood children in Bukit Kemuning Village, Batang Hari Regency, Jambi Province. This is suspected to be due to the suboptimal parenting provided by parents to their children. The objectives of this research are to: (1) determine the description of parental parenting; (2) determine the description of the social behavior of early childhood children; (3) determine whether there is a significant relationship between parental parenting and the social behavior of early childhood children in Bukit Kemuning Village, Batang Hari Regency, Jambi Province. This research is a quantitative approach study with a correlational research type. The population of this research consists of 37 parents who have early childhood children, while the sample is 24 people. The research sample was taken using area random sampling. The data collection technique uses a questionnaire with a questionnaire instrument. The data analysis technique uses the percentage formula and rank order. The results of this research indicate that: (1) parental parenting in Bukit Kemuning Village is still categorized as low; (2) the social behavior of early childhood children in Bukit Kemuning Village is categorized as low; (3) there is a significant relationship between parental parenting and the social behavior of early childhood children in Bukit Kemuning Village.Keywords: Parenting, Social Behavior, Early Childhood.